2004
DOI: 10.2514/1.10891
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Dose Rate Effects in Polymers Irradiated in Vacuum

Abstract: The most reliable information on polymeric material radiation resistance and lifetime may be obtained in tests conducted under operational conditions. An important problem of the environment simulation is the adequacy of the accelerated test results, because the dose rates used in the test and under operational conditions can differ by up to several orders of magnitude. Accelerated testing to determine operational engineering performance is valid only when the change in a material property does not depend on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
4
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 11 publications
3
4
0
Order By: Relevance
“…It is clear that the lower dose rate caused much more severe chain scission (reduction in conductivity) than the higher dose rate. This dose rate effect has been confirmed by others (Briskman et al, 2004).…”
Section: Effect Of Total Dose and Dose Rate On Surface Conductivitysupporting
confidence: 81%
“…It is clear that the lower dose rate caused much more severe chain scission (reduction in conductivity) than the higher dose rate. This dose rate effect has been confirmed by others (Briskman et al, 2004).…”
Section: Effect Of Total Dose and Dose Rate On Surface Conductivitysupporting
confidence: 81%
“…It is clear that the lower dose rate caused much more severe chain scission (reduction in conductivity) than the higher dose rate. This dose rate effect seen even in vacuum has been confirmed by others [Biskman, 2004]…”
Section: Resultssupporting
confidence: 81%
“…In addition, it was found that oxidative degradation was a possible explanation for the scission dominance at decreased dose rates. Other studies (Briskman, et al 2004, Gillen and Clough, 1981a, Gillen and Clough, 1989, Sasuga, et al, 1985, and Seguchi, et al, 1981 have also discussed similar findings of scission related effects due to oxidation at low dose rates. Given that this study is performed in air at two extreme dose rates, it is possible that the strain effects are also due to oxidative degradation occurring more heavily in the slow dose rate samples, giving rise to the increased strain behavior.…”
Section: Discussionsupporting
confidence: 53%